Nerve palsy following total hip arthroplasty using trochanteric osteotomy and proximal femoral shortening in Crowe Type 4 developmental dysplasia of the hip: a prospective cohort study - Afshin Taheriazam; Erfan Poursaleh; Ahmad Abbaszadeh; Mehdi Samberani; Parsa Taheriazam; Rezvan Darabi; Salar Baghbani (BMC Musculoskeletal Disorders)
Abstract Introduction Total hip arthroplasty (THA) is a cornerstone intervention for Crowe Type 4 developmental dysplasia of the hip (DDH), a severe form characterized by complete hip dislocation and acetabular deficiency. This study aimed to evaluate the incidence of nerve injury in patients undergoing THA via trochanteric osteotomy and proximal femoral shortening, with a secondary focus on the impact of prosthesis type (cemented vs. cementless). Material and method A prospective cohort study was conducted in Iran on 62 patients (81 hips) with Crowe Type 4 developmental dysplasia of the hip between 2020 and 2022. All procedures utilized a standardized direct lateral approach with trochanteric osteotomy and femoral shortening (3–4 cm). Nerve injury was assessed postoperatively via electromyography/nerve conduction velocity (EMG/NCV). Continuous variables were analyzed using independent t-tests, categorical variables with chi-square tests, and significance set at P < 0.05. Results In this study, ultimately, 46 patients (62 hips) completed the study according to the protocol. Among the participants, 54 cases (87.1%) were female and 8 cases (12.9%) were male. The mean age and BMI of patients were 40.35 years and 25.19 Kg/m2, respectively. Finally,59 cases (95.2%) were without any neurological deficit and 3 cases (4.8%) developed neurological problem during 12 months after surgery. The frequency of neurological deficit had a statistically significant correlation with the type of prosthesis (P = 0.01). Conclusion Trochanteric osteotomy with proximal femoral shortening achieves substantial leg lengthening in Crowe Type 4 developmental dysplasia of the hip, with minimal nerve injury risk. Cementless prostheses demonstrated superior neurological safety, advocating for their preferential use.